2014
DOI: 10.1039/c4ra08799b
|View full text |Cite
|
Sign up to set email alerts
|

Lewis acidic strength controlled highly selective synthesis of oxime via liquid-phase ammoximation over titanosilicates

Abstract: The Lewis acidity of titanosilicates determines oxime selectivity in ammoximation by influencing the reaction activation energy of Ti–OOH for the highly efficient formation of NH2OH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…The activation rate of H 2 O 2 to form the active Ti-OOH species (k 1a ) that serves as the most crucial step in titanosilicate-catalyzed oxidation processes depends greatly on the intrinsic catalytic ability of catalysts that is expressed as Lewis acidity. As a result, in comparison with the limited role of excessive NH 3 (k 1b ) in promoting the catalytic oxidation rate of H 2 O 2 for yielding NH 2 OH intermediate (k 1 ), the strong Lewis acidity of Ti active sites can accelerate the rate (k 1 ) fundamentally and then the competitive noncatalytic oxidation rate of oxime by H 2 O 2 (k 2 ) is further decreased even close to zero, because the reaction energy barrier could be strongly reduced with increased acidic strength of the catalyst [50,51]. Therefore, the Lewis acidic strength of titanosilicates is reasonably considered as the decisive factor in the highly selective synthesis of oxime among these influential factors.…”
Section: Influence Of Intrinsic Catalytic Activity Of Titanosilicatesmentioning
confidence: 98%
“…The activation rate of H 2 O 2 to form the active Ti-OOH species (k 1a ) that serves as the most crucial step in titanosilicate-catalyzed oxidation processes depends greatly on the intrinsic catalytic ability of catalysts that is expressed as Lewis acidity. As a result, in comparison with the limited role of excessive NH 3 (k 1b ) in promoting the catalytic oxidation rate of H 2 O 2 for yielding NH 2 OH intermediate (k 1 ), the strong Lewis acidity of Ti active sites can accelerate the rate (k 1 ) fundamentally and then the competitive noncatalytic oxidation rate of oxime by H 2 O 2 (k 2 ) is further decreased even close to zero, because the reaction energy barrier could be strongly reduced with increased acidic strength of the catalyst [50,51]. Therefore, the Lewis acidic strength of titanosilicates is reasonably considered as the decisive factor in the highly selective synthesis of oxime among these influential factors.…”
Section: Influence Of Intrinsic Catalytic Activity Of Titanosilicatesmentioning
confidence: 98%
“…Z. Zhuo et al reported that higher Lewis acidic strength of Ti active sites could promote the formation of NH 2 OH, 47 and NH 2 OH was thought as the reaction intermediate in ammoxidation benzene to aniline. 31,32,48 The formation of Ti-O-K might have negative impact on Ti site then the formation of NH 2 OH.…”
Section: Discussionmentioning
confidence: 99%
“…The hierarchical porous structure was much more effective in improving the catalytic properties of TS-1 zeolite for ketone ammoximation 38,39 because the orices on the surface of the catalysts could alleviate the diffusion limitations. Zhuo et al 40 demonstrated the relation between the Lewis acid strength in titanosilicate catalyst and the selectivity of oximes; TS-1 with stronger Lewis acidity provided better selectivity to oximes.…”
Section: Introductionmentioning
confidence: 99%